2015
DOI: 10.1111/jocd.12139
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative study on efficacy and safety of 1550 nm Er:Glass fractional laser and fractional radiofrequency microneedle device for facial atrophic acne scar

Abstract: Atrophic acne scars improved in both groups without significant side effects. Additionally, the fractional laser was a more effective treatment option for acne scars, but the fractional radiofrequency microneedle device offered good adherence and short downtime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 22 publications
5
84
1
Order By: Relevance
“…As for safety issues, the incidence of commonly observed, treatment-related side effects was not notably increased, as compared with NAF alone. FMR leads to only slight changes in epidermal barrier functions, resulting in shorter downtime (15). Severe side effects including secondary scarring and pigmentary changes were not observed in the current study.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…As for safety issues, the incidence of commonly observed, treatment-related side effects was not notably increased, as compared with NAF alone. FMR leads to only slight changes in epidermal barrier functions, resulting in shorter downtime (15). Severe side effects including secondary scarring and pigmentary changes were not observed in the current study.…”
Section: Discussioncontrasting
confidence: 56%
“…Finally, this study did not measure the efficacy of FMR alone for acne scars. However, a previous study reported that NAF is more effective for acne scars than FMR (15). Because our present study showed that the combination of NAF and FMR is superior to NAF alone, we can speculate that the combined treatment would also be more effective than FMR alone.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Therefore, the risk of dyspigmentation may be minimized. Studies utilizing fractionated radiofrequency on Asian skin types have demonstrated promising results in the treatment of atrophic acne scarring , periorbital wrinkles , photoaging , and striae . This large group of devices are valuable options in treatment of ethnic skin concerns, especially in combination with other modalities; however, their safety, efficacy, and indications are beyond the scope of this review.…”
Section: Fractionated Radiofrequency Devicesmentioning
confidence: 99%
“…Acne scarring is subject to skin rejuvenation through multiple EBDs. Filler injections are also considered another treatment option for acne scarring 21–27 . Treatment combinations have been developed to combat acne scarring such as lasers combined with RF, lasers combined with other laser types, and FRF in conjunction with filler injections 26–30 …”
Section: Tissue Enhancers In Combination With Rfmentioning
confidence: 99%